Revision of Civil Law: Challenges and Opportunities in The Modernization of The Legal System - Abu Sahman Nasim; Olyvia Rosalia (Leges Privatae, 2025)
The revision of the Indonesian Civil Code, inherited from Dutch colonial law, has become an urgent necessity in responding to the dynamic development of society, economy, and technology. This normative legal research aims to analyze the fundamental challenges faced in the process of revising the Civil Code, as well as the strategic opportunities that can be utilized to modernize the legal system. Through a normative-juridical approach supported by literature studies, legal documents, and comparative law analysis, this study identifies key weaknesses in the current Civil Code, such as outdated norms, lack of digital regulation, and inadequate protection for contemporary civil relations. The research also reveals the potential benefits of integrating digital law, simplifying legal procedures, recognizing local customary laws, and embedding the principle of justice to enhance legal relevance and responsiveness. The findings of this study offer theoretical and practical recommendations for stakeholders involved in legal reform efforts, emphasizing that modernizing civil law must be grounded in Indonesia's socio-cultural context while embracing global legal developments.